Motivação dos alunos da área de estética em curso oferecido na modalidade a distância: contribuições para processos educativos em saúde - Pela, Flavia Maria Pirola [UNIFESP] (2021)
Science plays a crucial role in society, being responsible for the discovery, production and dissemination of knowledge. In other words, we use science and technology to facilitate and improve people's lives. Non-face-to-face education has, for a long time, revolutionized the pedagogical plans of almost the entire world, in both developed and developing countries, either in the context of formal education or in the areas of professional training through distance education (EaD). The purpose of this research is to identify the students' perception related to motivation of learning in the Aesthetics and Cosmetics under graduate distance course at University Cruzeiro do Sul. This study is quantitative with retrospective analytical/descriptive design and was based on Motivation Strategy Questionnaire for Learning (MSLQ), an instrument that consist in 17 questions designed from the classical theories of social cognitive learning, and which are widely used to predict academic performance. MSLQ was applied in a group of 422 respondents, with return on a type Likert scale, from 1 to 7, through anonymous responses, verifying the level of reliability of the research by presenting an acceptable Cronbach’s alpha. It is noticeable that teaching strategies in addition to the relationship between teacher and student and obtaining good grades, in EaD environment, directly influence the quality of teaching and the motivation of students, and when maintained for a prolonged period of time, make it possible for this group to remain motivated and willing to develop their studies in an organized manner, enhancing the learning.